Temporary help employment in recession and recovery - Susan N. Houseman; Carolyn J. Heinrich (W.E. Upjohn Institute for Employment Research, 2015)
The temporary help industry, although small, plays a significant role in the macro economy, reflecting employers' growing reliance on temporary help agencies to provide flexibility in meeting staffing needs. Drawing on detailed temporary-help order data between 2007 and 2011 from a large, nationally representative staffing company, we provide insights into the characteristics of temporary help work, employers' use of temporary agencies to screen workers for permanent positions, and the industry's role in labor market adjustment over the business cycle. We estimate that the temporary help industry accounted for a large share of gross job losses and job gains over this period, as well as for a sizable share of net separations and hires. Nearly a third of assignments were observed to end prematurely due to worker performance problems (largely soft skills deficiencies) or quits, and hire rates of workers in temp-to-hire contracts were low. Although most temporary help assignments are short-lived, during the recession, companies lengthened temporary help assignments and reduced hiring from their pool of temps, possibly in response to economic uncertainty. Nominal wage growth among new temporary hires was weak over the five-year period and failed to keep pace with inflation.
Keywords: J23; J21; J49; 330; temporary help employment; business cycle